Developing Promotional Media by Creating Video Advertisement on Tiktok Using The Capcut Pro Application for Annida Catering Batu - Haekal Adli Muhammad; Joni Dwi Pribadi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Annida Catering, located in Bumiaji, Batu City, provides catering services for various events. Its digital promotions, especially video content on TikTok, have been ineffective due to a lack of appeal. This study aims to create advertising videos using the CapCut Pro application as a promotional medium to enhance attractiveness and reach. The research used the Action Research method with respondents consisting of the business owner, marketing experts, multimedia experts, consumers, and potential consumers. The questionnaire results, using the EPIC model, showed a score of 4.4, which falls into the highly effective category. In conclusion, the advertising videos created were proven to be effective promotional media and can help increase audience reach.